PENGARUH AKUNTABILITAS, GENDER, DAN PENGALAMAN KERJA AUDIT TERHADAP KUALITAS HASIL KERJA AUDITOR DENGAN PENGETAHUAN SEBAGAI VARIABEL MODERASI (Studi Empiris pada Kantor Akuntan Publik di Medan, Padang dan Pekanbaru) - Muhammad Reza Fahlevi; Hardi '; Julita ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to obtain empirical evidence about the influence of accountability, gender, auditor work experience and knowledge to the extent of quality of auditor’s works. It is also predicted that knowledge moderate the relationship between accountability, gender, auditor work experience with quality of auditor works’s. This study used primer data with quitonaiers. The population of this study was obtained from a sample of auditors who work for local Accounting Public Firm in Pekanbaru, Padang and Medan. By using purposive sampling method, from 100 quitonaiers, 17 was not back and 14 quitonaiers did not used, so 68 auditors were selected as a sample. The analysis technique used multiple linear regression analysis using SPSS ver. 17 computer program. The results of analysis showed that accountability, gender, auditor work experience, accountability after moderated with knowledge and auditor work experience after moderated with knowledge significantly influence to the extent of quality of auditor’s works. Meanwhile, the results of analisys also showed gender after moderated with knowledge had not significantly affected the extent of quality of auditor’s works with tcount -1,957 and it belowed ttable 1,995 and signification value 0,355 .Based on total Adjusted R-Square result 62,6% while the rest 37,4%Keyword : quality of auditor’s works, accountability, gender, auditor work experience, knowledge